Influence of exogenous phytohormones, methyl jasmonate and suppressors of jasmonate biosynthesis on Agrobacterium-mediated transient expression in Nicotiana excelsior - Sindarovska, Y.R.; Gerasymenko, I.M.; Kuchuk, M.V.; Sheludko, Y.V. (Вiopolymers and Cell, 2012)
Our aim was to investigate the influence of some exogenous agents on the recombinant protein accumulation in plants via Agrobacterium-mediated transient expression. Methods. Agrobacterium-mediated transient expression method, spectrophotometric methods for protein analysis, statistical calculations. Results. It was shown that the tested compounds in different concentrations (namely, auxins, cytokinin, methyl jasmonate and suppressors of jasmonate biosynthesis (phenidon and diethyldithiocarbamic acid)) added to the infiltration buffer did not influence either GFP transient expression nor total protein accumulation in plant tissue. Conclusions. The results suggest that the tested factors are not substantial for Agrobacterium-mediated transient expression. Keywords: Nicotiana excelsior, Agrobacterium, transient expression, GFP.